Assessing land titles application and uptake in regularised informal settlements in Tanzania. Issue 3 (2nd September 2018) - Kusiluka, Moses M.; Chiwambo, Dorice M.
ABSTRACT: Informal settlements are increasingly becoming a concern for many developing countries. Most of the people living in informal settlements do not have formal property ownership documents. As a result, properties in such settlements have relatively less value and security of tenure and thus can hardly be used as collateral for credit. Giving property owners formal land ownership documents through informal settlements regularisation is one of the measures to address the problem. Using six regularised settlements in Tanzania and employing institutional approach, this paper identifies and assesses factors affecting land title application and uptake. Findings show that title application rate and uptake are still low mainly due to inhibitive institutional constraints such as negative customs and beliefs; poverty; high lending rates; low financial literacy; land related taxes and charges and; outdated laws. These findings underscore the imperativeness of undertaking a comprehensive institutional environment analysis while designing and executing regularisation projects.